Student's Voices in Language Courses in Tertiary Education: Giving Power to Students - Hadjiconstantinou, Panayiota; Efthymiou, Fotini (My University, 2024)
This paper focuses on teaching and learning practices in language courses in Tertiary Education, through which the students take the subject position (Fairclough, 1989). It takes into account the point that European Values must be substantially incorporated into Education. It also emphasises the fact that all students’ cultures can be utilised in language courses. Moreover, it strongly agrees with the statement that language can transform society and can be transformed by it (Stamou, 2014). It specifically advances that students in environments that renounce traditional methods of teaching/learning (which are connected to the Colonial Era and the related power of the dominant groups), become researchers, designers, self-reflectors, decision-makers, re-designers, and creators of their multimodal texts, through processes which make their voices heard and consequently incorporate their identities in their texts. In these teaching and learning practices, students’ interests, concerns, beliefs, and goals along with their imagination and creativity, are integral components to express their voices. These practices aim to convince students that as creators of texts, they are the ones who have the power to act as social actors (the students as principals, authors, and animators, Goffman 1981, cited in Fairclough, 2004). The main outcomes of these practices are related to the realisation that all cultures include socially constructed norms of behaviour, values, representations of the social and natural world, and language varieties. All the aforementioned are equally valuable and can be used in texts, based on the text creator’s social goal. Moreover, the students realised that the language and the other semiotic modes are pools from which the users draw the elements needed, in order to create the message they want to convey. Finally, students’ language-communication skills were improved through the analysis, re-design and re-creation of their texts. The practices included in this work were implemented in: 1. The Intensive Greek Language and Culture Course I-Foundation, (addressed to African Students), 2. The English for Specific Purposes for Multimedia and Graphic Arts I Course (English for Specific Purposes), (addressed to audiences with a large percentage of Greek-Cypriot students). All the above-mentioned practices were evaluated both by the student-participants and the language instructors. The theories/approaches that this study was drawn upon are: Systemic Functional Grammar (SFG), (Halliday, 1978), Genre Theory (Cope & Kalantzis, 2014), Critical Literacy (Baynham, 2002; Freire 1974), Multiliteracies (Cazden, et al., 1996), Critical Discourse Analysis (CDA) (Fairclough 2004; 2001; 1989), Classroom Discourse (Duff, 2010; Ioannidou, 2014) and Classroom Ethnography (Cazden, 1988; Hammersley, 1990; Hymes 1989).
Keywords: language courses; Tertiary Education; students’ voices; students’ power